Pemenuhan Hak Anak Dan Keluarga Pada Kasus Korban Penyebaran Pornografi Di Dinas Ppa Kota Medan - Destin Aulia Alma; Tuti Atika (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This journal explores the fulfillment of children's and family rights in the context of handling cases of victims of pornography dissemination at the Department of Women and Child Protection (Dinas PPA) in Medan City. The evaluation is conducted through final mediation to understand the progress experienced by clients in dealing with their cases. The mediation results indicate that the case is in the final trial stage, with positive information that the victim, who is a minor, has returned to school. However, the psychological impact on the victim remains a concern. The processes and assistance provided by the Dinas PPA demonstrate a positive impact at the micro level, aiding individuals directly, as well as at the macro level by contributing to improved public policies related to child and women protection. This journal illustrates the crucial role of the Dinas PPA in creating a safer and more responsive environment for human rights.